AKUMULASI KAPITAL DAN EKSISTENSI NEGARA: ANALISIS PEMBERDAYAAN KELOMPOK WANITA NELAYAN (KWN) DI KELURAHAN PATTINGALLOANG KOTA MAKASSAR - Ruslin, Ismah Tita; Zainal, Nur Aliyah (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2019)
This study examines the formation of capital accumulation in a fishing community driven by women (fishermen's wives) and is able to produce socio-economic changes in the community. The research, located in Pattingalloang Sub-District, aims to find out the pattern of capital accumulation and the role of state in the Fishermen Women's Community (KWN) Fatimah Az-Zahrah. The research was analyzed with capital accumulation theory, structuration, social networks and the state and social democracy. The research method was carried out qualitatively with a phenomenological approach, which primary data was obtained through observation and in-depth interviews, while secondary data obtining from various literature, supporting documentation and archives that strengthen primary data. Data analysis techniques derived from words and spoken words from the observed actors. The results, illustrate the pattern of capital accumulation in terms of actors, place the women as empowerment agencies, initiation of empowerment, named Nuraeni and several women so that the Woman Fishermen Community was born, with government and non-government parties. The role of government in the formation of capital accumulation in KWN can be divided into three important roles, namely; division of power, the provider of legal certainty and social security service providers.